2004
DOI: 10.1896/1413-4411.6.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Bathing Behavior of Giant Anteaters (Myrmecophaga tridactyla)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…The disruption of dispersal behaviour can lead to the endangerment and potential extinction of isolated populations by various mechanisms, including changes to genetic diversity and structure (Keyghobadi ), stochastic threats (Fischer and Lindenmayer ) and long‐term displacement effects (Ewers and Didham ). Using CTs to document dispersal behaviour can improve understanding of responses to movement disruption (Blumstein and Fernández‐Juricic ) and inform design and implementation of mitigation measures that encourage dispersal.…”
Section: Emerging Directions In Camera‐based Conservation Behaviourmentioning
confidence: 99%
“…The disruption of dispersal behaviour can lead to the endangerment and potential extinction of isolated populations by various mechanisms, including changes to genetic diversity and structure (Keyghobadi ), stochastic threats (Fischer and Lindenmayer ) and long‐term displacement effects (Ewers and Didham ). Using CTs to document dispersal behaviour can improve understanding of responses to movement disruption (Blumstein and Fernández‐Juricic ) and inform design and implementation of mitigation measures that encourage dispersal.…”
Section: Emerging Directions In Camera‐based Conservation Behaviourmentioning
confidence: 99%
“…The salivary glands of Giant Anteaters appear to be active only when feeding. Giant Anteaters drink frequently and when the water table drops below the surface they may even dig to access water sources, in the process habilitating them for other mammal species (Emmons et al 2004).…”
mentioning
confidence: 99%
“…Emmons et al (2004) documented the bathing behaviour of Giant Anteaters, noting that they did so during the night but were unable to reach a conclusion as to why the animals bathe given that they do not fit the profile of typical bathing mammals. They did however add that captive animals apparently enjoy being hosed down and even aggressively compete for spaces under the spray.…”
mentioning
confidence: 99%
“…It is possible that the wide variety of serovars observed in anteaters from SESC (Fig.1), as well as in domestic animals and other wildlife from this area (Freitas et al 2010;Jorge et al 2011), is related to the area having favorable conditions for the survival of Leptospira in the environment, such as seasonal flooding and high temperature and humidity levels (Acha & Szyfres 2003). Emmons et al (2004) repeatedly observed giant anteaters wallowing in mud and bathing in shallow ponds that are used by other species as watering place. This behavior may further increase the risk of anteaters becoming infected with L. interrogans.…”
Section: Discussionmentioning
confidence: 99%